RETRACTED: Parthenolide Augments the Chemosensitivity of Non-small-Cell Lung Cancer to Cisplatin via the PI3K/AKT Signaling Pathway - Wu, Li-Mei; Liao, Xiao-Zhong; Zhang, Yan; He, Zi-Rui; Nie, Shi-Qing; Ke, Bin; Shi, Lin; Zhao, Jian-Fu; Chen, Wen-Hui (Frontiers in Cell and Developmental Biology, 2021)
The mortality rate of non-small-cell lung cancer (NSCLC) remains high worldwide. Although cisplatin-based chemotherapy may greatly enhance patient prognosis, chemotherapy resistance remains an obstacle to curing patients with NSCLC. Therefore, overcoming drug resistance is the main route to successful treatment, and combinatorial strategies may have considerable clinical value in this effort. In this study, we observed that both parthenolide (PTL) and cisplatin (DDP) inhibited the growth of NSCLC cells in a dose- and time-dependent manner. The combination of PTL and DDP presented a synergistic inhibitory effect on NSCLC at a ratio of 50:1. The combination of PTL and DDP synergistically inhibited cell migration and invasion, inhibited cell cycle progression and induced apoptosis of A549 and PC9 cells. Bioinformatics and network pharmacology analysis indicated that PTL may primarily affect the phosphatidylinositol 3-kinase (PI3K)-AKT signaling pathway. After treatment with PTL and DDP alone or combination, Western blot analysis revealed that the proteins levels of Bax and cleaved Caspase-3 were upregulated, while p-PI3K, p-Akt, Caspase-3, and Bcl-2 proteins were downregulated. Among these alterations, the combination of PTL and DDP was found to exhibit the most significant effects. PTL might therefore be considered as a new option for combination therapy of NSCLC.